A time and motion study in outdoor patient department of rural health training centre of tertiary medical college in Konkan region, India - Chopade, Rahul Rajaram; Sharma, Narendra K.; Sundar, Suresh M. (International Journal Of Community Medicine And Public Health, 2019)
Background: Purpose of time motion study is to know the time taken in different service delivery points in outpatient department (OPD), for specific activity, work function or mechanical process and to assess the perception of beneficiaries regarding the total time spent in the OPD. Therefore, the present study was conducted to study the operational efficiency and also to find the time required for various activities at different service points at rural health training centre attached to medical college. Methods: It was a cross-sectional study carried out in rural health training centre attached to BKL Walawalkar rural medical college, Sawarde), district Ratnagiri, Maharashtra, India over period of 6 month from July 2018 to December 2018. About 300 patients were included in the study. Results: According to 26.67% study participants, total time was too long. 26% study participants were not satisfied about the total time taken in the OPD while 50.34% study participants were satisfied regarding the total time. Conclusions: Patients satisfaction is the most important criterion to be met if more people are to be drawn into the hospital. Thus, improving the satisfaction of patients towards health care services by reducing their waiting time, by attending the patient in time will help to create a positive image of hospital in the mind of people and community.